IMPLEMENTASI MANAJEMEN USAHA TERHADAP PENDAPATAN USAHA MIKRO - Lakoro, Fibriyanti S; Sukrianto, Sukrianto; Latif, Samin (JURNAL CAPITAL : Kebijakan Ekonomi, Manajemen dan Akuntansi, 2024)
Micro businesses in Tilamuta District make the Boalemo Regency Government collaborate with banking institutions to distribute people's business credit to be able to support and develop micro businesses in Tilamuta District. This research aims to determine the impact of business management on micro business income in Tilamuta District. The research method used is descriptive research with a qualitative approach. The types of data used are primary data and secondary data. Data collection techniques using observation, interviews and documentation. The data analysis technique used is interactive analysis using qualitative research consisting of data reduction, data presentation and data conclusion drawing. The results of the research are that business capital and competition are determining factors in increasing micro business income in Tilamuta District. Another factor is that old businesses must be able to increase income, in addition to the use of technology and digitalization in carrying out their business activities.